Civic consciousness as a matter of disciplinary discursive practices in Russia - Shevchenko, Olga M.; Volkov, Yuriy G.; Lubsky, Anatoly V.; Dyachenko, Angela N.; Glushkova, Svetlana A. (International Journal of Engineering and Technology, 2018)
Comprehension of theoretical discourse devoted to study of civic consciousness in Russia will make it possible to identify methodological alternatives in researching this phenomenon and construct the most optimal multidimensional and methodological field for investigating civic consciousness devoid of paradigm limitation within the context of tasks facing the country related to formation of civic patriotism and civic identity. In order to implement this research conception, a critical analysis strategy of civic consciousness knowledge with the identification of paradigm features that have arisen in the scientific and research practices obtained in various subject domains, is proposed in the article. The discursive analysis results have shown that the concept of civic consciousness as an integral social phenomenon, which determines the cognitive need for the development of a multidimensional methodological construct of the wholism study of civic consciousness in Russia is being lost in the disciplinary scientific and research practices.Â Â